Limits to the Growth and Size of Firms - Penrose, Edith (American Economic Review, 1955)
There are two approaches to the question of the size of firms. the traditional approsch attempts to explain size in terms of the balance of advantages and disadvantages of being a particular size. Another approach emphasizes the process of growth and treats size as a more or less incidental result of a continuous on -going or unfolding process. The author wants here to suggest an alternative growth approach which, in common with the biological variant, insists that a predisposition to grow is inherent in the very nature firms, but which, in contrast, makes growth depend on human motivation.